The Impact of One Belt One Road and Indonesia-Pakistan Palm Oil Trade Liberalization - Widyastutik; Amaliah, Syarifah; Hotsawadi; Firdaus, Muhammad (Jurnal Manajemen & Agribisnis, 2023)
This study focused more on analyzing the impact of the One Belt One Road initiative combined with the scenario of turning Pakistan into Indonesian palm oil trade and investment hub in the Central Asia, South Asia and Middle East Regions on Indonesia's macroeconomy. The analytical method in this study used GTAP model version 9, with reference year 2011. The results showed that the One Belt One Road initiative combined with the scenario of turning Pakistan into Indonesian palm oil trade and investment hub in the Central Asia, South Asia and Middle East Regions has led to an increase in various components of Indonesia's and Pakistan's macroeconomic variables. However, the benefits received by Indonesia in various components of macroeconomic variables are greater than those of Pakistan. Keywords: One Belt One Road, GTAP, macroeconomy, Pakistan